Time series analysis of low-concentration air pollution and hospital respiratory disease outpatient visits - Wang, Yongxin; Chen, Jingwen; Zhou, Quan; Kang, Shuling; Jiang, Yu; Xiang, Jianjun; Wu, Jing; Li, Jin; Chen, Zhiwei; Wu, Chuancheng (Frontiers in Public Health, 2025)
ObjectiveThe aim of this study was to analyze the effects of short-term exposure to low concentrations of air pollutants on the volume of respiratory outpatient visits in hospitals and their lagged effects.MethodsThe study collected outpatient data from seven hospitals in Fuzhou City, air pollution data provided by the Fuzhou Environmental Monitoring Center Station, and meteorological data from the Fuzhou Meteorological Bureau for analysis from 2019 to 2022. Time series analysis was used to explore the relationship between air pollutants and meteorological factors and daily outpatient visits for respiratory diseases by constructing a generalized linear model (GLM).ResultsFrom 2019 to 2022, the total outpatient volume of respiratory diseases in 7 hospitals in Fuzhou was 1,530,000, with pediatrics accounting for 72.44% and internal medicine accounting for 27.56%. Air pollutants such as PM2.5, PM10, NO2, and SO2 all had significant impacts on the total respiratory and pediatric respiratory outpatient volumes. NO2 and PM10 had the greatest impact on respiratory diseases on the day of pollution exposure or 1 day later, while SO2 and PM2.5 exhibited longer lag effects, with the most significant impact occurring at a lag period of 4–6 days. The impact of air pollution on pediatric respiratory disease outpatient visits was generally more significant than that on adult.ConclusionLow concentrations of air pollution significantly impacted respiratory outpatient visits in Fuzhou, especially in children. Despite relatively good air quality, air pollution in low-pollution areas poses a public health risk, highlighting the need for targeted pollution control policies.